El espacio público como respuesta a la sobredemanda generada por el turismo en el municipio de Calima Darién (2024)
The following research aims to address the problem generated by tourism in public spaces in the Municipality of Calima Darién, based on how it affects the local population in the urban environment and how they coexist with this population in all aspects related to the urban environment.